Estimation of production consistency of diphtheria, tetanus, and pertussis components of the DTP vaccine using Shewhart charts - I. A. Alekseeva; O. V. Perelygina; E. D. Kolyshkina (Биопрепараты: Профилактика, диагностика, лечение, 2021)
The Russian Federation puts special emphasis on vaccination-related issues, in accordance with the WHO recommendations. The fact that vaccination, in particular with the diphtheria, tetanus, and pertussis vaccine (DTP vaccine), covers large population groups, accounts for the relevance of research aimed at improving the quality of vaccines. One of the ways to produce vaccines of assured quality is to maintain consistent manufacturing processes that ensure consistency of product characteristics. The stability of the technological processes may be assessed using Shewhart charts. The aim of the study was to assess the production consistency of diphtheria, tetanus, and pertussis components of DTP vaccine using Shewhart control charts. Materials and methods: the study used data from 60 batch summary protocols of a Russian-produced DTP vaccine that were submitted to the Testing Centre of the Scientific Centre for Expert Evaluation of Medicinal Products from September 2017 until April 2020. The study assessed one of the main vaccine quality characteristics—specific (protective) activity of diphtheria, tetanus, and pertussis components. Shewhart charts for the diphtheria and tetanus components were constructed based on the manufacturer’s summary protocols, while Shewhart charts for the pertussis component were constructed based on both summary protocols and the results obtained by the Testing Centre during certification of the product batches. The Shewhart charts were used in accordance with the national standards GOST R 50779.42-99 and GOST R ISO 7870-2-2015. Results: a retrospective analysis of R- and X-charts covering a 2.5-year period revealed some characteristic trends in special-cause criteria. The most alarming situation was observed for the production of the diphtheria component. The technological processes were somewhat safer in the case of the tetanus and pertussis components. The production process lacked due statistical control, which is confirmed by the lack of correlation between the results of the pertussis component activity assessment obtained by the manufacturer and the Testing Centre. Conclusions: during the analysed period, the production of the diphtheria, tetanus, and pertussis components of the DTP vaccine was not always consistent. This highlights the need to conduct research aimed at standardisation of both production processes and control test conditions.